Effect of Adding Different Levels of Antioxidant and Imported Ginseng (Panax) Roots to The Diet in The Microbial - Doaa Mohammed; Ali Jawad Enouz; Ammar Hussein Jawad Areaaer (Kufa Journal for Agricultural Sciences)
The current study was carried out on a poultry farm that belongs to the Animal production department - College of Agriculture - University of Kufa, for the period from September 10, 2020, to October 14, 2020, for a period of 5 weeks, in which the effect of adding the ascorbic acid as antioxidant and ginseng root powder was studied. Red Ginseng (Panax) to reduce the effects of heat stress for broilers, the experiment included 420 unsexed Ross-308 chicks, one day old, with an average initial weight of 40 g, prepared from private hatcheries in the governorate of Babylon (Al-Anwar Al-Muradia hatchery). The chicks were divided into 7 treatments included for each Treatment of 60 chicks, with 3 replicates (each replicate is 20 chicks), and the treatments were divided as follows: T1: Standard (Control) without adding. T2, T3 and T4 were given 2, 4 and 6 g ginseng / kg of feed respectively, T5, T6, and T7 were given 2, 4 and 6g ascorbic acid /kg of feed respectively. The chicks were fed with starter diet for the duration of 1-21 days and finisher diet for the duration of 22-35 days. The results of the statistical analysis indicated that there was a highly significant (p<0.01) decrease in the numbers of Escherichia coli bacteria to T7, T6, T4, and T3 the treatments birds compared with the control treatment. The results also indicated a highly significant (p<0.01) increase in the numbers of Lactobacillus bacteria in T7 treated birds, T6, T5, T4 compared with the control treatment.